Survey of literature on crevice corrosion (1979-1998) : mechanisms, test methods and results, practical experience, protective measures and monitoring - IJsseling, F. P. (IOM Communications, 2000)
Crevice corrosion is a complex and technically interesting corrosion mechanism but its commercial significance should not be ignored. This survey, the most complete overview on crevice corrosion available today, covers many alloys which can suffer crevice attack but focuses mainly on stainless steels. The survey covers mechanisms, test methods and results, practical experience, protective measures and monitoring.
"Book number 745."
Keywords: Stainless steel -- Corrosion.; Seawater corrosion.; Alloys -- Testing.; elektronické knihy; electronic books